Analisis Profitabilitas dan Solvabilitas Untuk Mengukur Kinerja Keuangan di PT. Indofood Sukses Makmur Tbk. - Regita Cahyani Annisa Putri; Nadhirah Lathifunnisa; Sharen Syifa Nafia; Aliefthio Putra Rindjani Hoefnagel (Jurnal Riset Akuntansi, 2023)
Good company financial performance continues to be demanded in order to maximize profits in achieving its goals. This study was conducted to analyze the financial performance achieved by PT Indofood Sukses Makmur Tbk. in 2019-2021. The approach used in this research is a quantitative descriptive study. The type of data is secondary data which can be obtained through the financial statements of PT Indofood Sukses Makmur Tbk. in 2019-2021. The analysis in this study used profitability ratios and solvency ratios. The results showed that for 4 years it was in a fairly good financial performance condition. The company's profitability in terms of the GPM indicator is in good condition, but the ROA indicator is in a poor condition. The company's solvency both in terms of DER and DAR indicators is in very good condition.